Pengaruh Kepemimpinan, Pelatihan, Dan Kompensasi Terhadap Kinerja Karyawan (Studi Empiris Pada PKU Aisyah Boyolali) - Riwanto, Atok; , Dr. Soepatini, SE., M.Si (2016)
The aim of this study is to analyze the influence of leadership, training, and compensation on employee performance. Population of this study is all of non-medical hospital staff of PKU Aisyah Boyolali. Based on purposive sampling 49 employees observation were selected as sample of this study. This study used a quantitative approach, the data was obtained from questionnaires filled out by respondents with multiple regression as a method of analysis. The study showed that leadership has an significant and positive effect on employee performance. Training significantly and positively influences on employee performance. Compensation has an insignificant and negative effect on employee performance. Simultaneously leadership, training, and compensation has a significant influence on employee performance with the contributions made (R2) of 40.1% and the rest is explained by other variables.